Using Games to Improve Students’ Active Involvement in the Learning of English Syntax at IAIN Madura: An Autonomous Learning - Abdul Wafi (IAIN MADURA, 2019)
Learning English syntax is taken as a boring subject for the majority of students since the activities frequently monotonous and the classroom setting becomes quiet and too formal. The study is intended to discover the use of games in the learning of English syntax. It is conducted to find out whether the games provided by students themselves (autonomously) are able to make a joyful learning activities and able to increase their involvement in the learning process. The study makes use descriptive research which is classified into a case study. The data are collected through classroom observation, questionnaire to gain students’ response toward the classroom learning activities. The research subjects are the students of 5th semester at English department IAIN Madura who join in English syntax class. The researcher focuses on D class, with 33 students, where the time schedule for the learning is at 13.00 in the afternoon. From the data result, it is found that the use of games, which are prepared by the students autonomously, is able to make the class more joyful and able to increase their active involvement in the learning activities. Making this study distinctive from other studies is the games are provided by the students themselves instead of being provided by the lecturer. So, learning autonomy is really there. The lecturer only gives them a clear rule that is the learning activities should be made joyful by using any games related to the topic being discussed.